2015
DOI: 10.1007/s10940-015-9258-5
|View full text |Cite
|
Sign up to set email alerts
|

Crime, Employment and Social Welfare: An Individual-Level Study on Disadvantaged Males

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 65 publications
4
8
0
1
Order By: Relevance
“…One study among formerly incarcerated adults (Makarios et al, 2010) showed that besides employment, receiving social benefits also reduced crime. This result was also found in two studies among previously institutionalized youth (Mesters et al, 2016; Verbruggen et al, 2015). However, a study among formerly incarcerated adult females indicated that receiving social benefits was not related to differences in criminal behavior (Rodermond, 2018), while another study among formerly incarcerated adults indicated that receiving benefits increased rather than decreased the odds of a reconviction (Skardhamar & Telle, 2012).…”
Section: Previous Researchsupporting
confidence: 85%
“…One study among formerly incarcerated adults (Makarios et al, 2010) showed that besides employment, receiving social benefits also reduced crime. This result was also found in two studies among previously institutionalized youth (Mesters et al, 2016; Verbruggen et al, 2015). However, a study among formerly incarcerated adult females indicated that receiving social benefits was not related to differences in criminal behavior (Rodermond, 2018), while another study among formerly incarcerated adults indicated that receiving benefits increased rather than decreased the odds of a reconviction (Skardhamar & Telle, 2012).…”
Section: Previous Researchsupporting
confidence: 85%
“…This study also found evidence suggesting that the duration of unemployment was positively related to property crime. Similar patterns were observed in a Dutch study (Mesters, van der Geest, and Bijleveld 2014), where regular employment (but not temporary employment) was negatively associated with property crime but unrelated to violent crime. Attending to the duration of both employment and unemployment, and using both random and fixed effects models, Verbruggen, Blokland, and van der Geest (2012) found employment to be associated with lower levels of offending among males and females, but employment duration was significant only for males.…”
Section: Job Exits: Research On Unemployment and Crimesupporting
confidence: 84%
“…Trimbur (2009) reported that employment reduced recidivism tendency and facilitate ex-offender's adjustment to civilian life in several ways. According to Mesters, van der Geest, and Bijleveld (2014) the probability of criminal behavior amongst ex-offender's reduces significantly when employed. First, employment provides ex-offenders an opportunity to earn wages, which helps to pay for transportation, food, and other daily expenses and may enable them to rebuild lost relationships with children and family.…”
Section: Advantages Of Employmentmentioning
confidence: 99%